A KEGIATAN BELAJAR MENGAJAR BERHITUNG DAN PENGADAAN POJOK BELAJAR PAUD AL-MADINAH DESA SESULU - Nofan, Nofansyah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Teaching and learning to count is an important activity to create a sense of wanting to understand the fun world of numbers so that children can feel enthusiastic and interested in learning to count. The aim of teaching and learning to count is to understand addition and subtraction, create a new playing learning atmosphere, and also provide learning facilities such as an abacus, reading books, and bookshelves. There are two methods used in teaching and learning activities, namely, the learning and playing methods, where the learning method is carried out using reading books and an abacus, while the playing method is carried out by holding quizzes. By holding teaching and learning activities, preschool children can better further develop their interest and talent in counting. Thus, it is hoped that this activity can provide benefits fot preschool children in the future, starting from developing academic, achievement, knowledge, memory, and speed in calculating.